Electron-impact excitation of krypton: cross sections of interest in plasma modeling - Gangwar, Reetesh Kumar; Sharma, Lalita; Srivastava, Rajesh; Stauffer, Allan D. (Physical review. A, Atomic, molecular, and optical physics, 2010)
We have performed relativistic distorted-wave calculations to study the excitation of Kr from its ground 4p6 configuration to the higher lying fine-structure levels of the 4p54d, 4p55p, and 4p56s manifolds. We have obtained relativistic Dirac-Fock multiconfiguration wave functions for the ground and the excited states. We present results for differential cross section and compare these with the available experimental measurements for energies up to 100 eV. We also report integrated cross sections for incident electron energies up to 300 eV and provide analytic fits for plasma modeling applications.